DEVELOPING ORAL COMMUNICATION SKILLS IN PRIMARY ENGLISH EDUCATION THROUGH INTERACTIVE CLASSROOM ACTIVITIES (SCIENCE TIME JOURNAL, 2026)
The development of speaking ability is a goal of foreign language instruction in primary education. Young learners need chances to communicate, interact and express ideas confidently in classrooms. This article looks at how interactive classroom activities improve communication skills among primary school pupils. The study focuses on learner-centered techniques like pair interaction, storytelling, group discussion, language games and collaborative tasks. A qualitative classroom-based approach was used to observe how communicative practices influence learners’ fluency, confidence, vocabulary use and participation. The findings show that interactive activities create a learning atmosphere where children feel motivated to speak without fear of mistakes. The article discusses how teachers can organise tasks effectively to encourage meaningful language use and active classroom engagement.